Clinical characteristics of moderate–severe obsessive–compulsive disorder in children and adolescents in China - Liyuan Luo; Bin Feng; Senjun Yang; Ning Zhang; Shengliang Qiu (Journal of International Medical Research, 2020)
Objective This study reports clinical characteristic of moderate–severe obsessive–compulsive disorder (OCD) among school students in China. Methods We examined 153 patients for the distribution of OCD symptoms using the Yale-Brown Obsessive Compulsive Scale Symptoms Checklist, the severity of anxiety and depression symptoms using the Hamilton Anxiety Scale and the Hamilton Depression Scale-24, respectively, and impairment in learning, family and social functions using the Pediatric Quality of Life Enjoyment and Satisfaction Questionnaire. Results The number of total OCD, obsession and compulsion symptoms was 6.71 (standard deviation [SD] = 2.25), 3.77 (SD = 1.32) and 2.94 (SD = 1.59), respectively. The incidence of moderate and severe depressive symptoms for junior high school students was significantly higher than for primary and high school students. The number of children and adolescents with OCD increased with age, reaching a peak in the senior high school stage. Conclusion The most common symptoms in children and adolescent OCD patients are miscellaneous obsessions, aggressiveness, religiousness, checking, miscellaneous compulsions, cleaning-washing and repeating. These patients show a relatively high co-occurrence rate of anxiety symptoms and depressive symptoms, which impairs their learning, as well as their family and social functions.